(untitled) (Homiletic, 2017)
This article asks how preaching might be understood as something akin to a mystical practice. To consider this, I do a close reading of a sermon by the medieval preacher and mystic Meister Eckhart. I read Eckhart’s sermon through the lens of Fred Craddock’s homiletic theory. Particularly important for this is Craddock’s suggestion that preaching does more than communicate ideas to its audience; rather, it can serve to lead its audience to an experiential awareness of its message. Interpreting Eckhart’s sermon in this way provides a sense of how preaching can indeed function as a mystical practice, bringing its listeners to a consciousness of their oneness with God.